Comparison of Clinical and Radiographic Outcomes of Laminoplasty, Anterior Decompression With Fusion, and Posterior Decompression With Fusion for Degenerative Cervical Myelopathy: A Prospective Multicenter Study. Issue 20 (15th October 2020) - Inose, Hiroyuki; Yoshii, Toshitaka; Kimura, Atsushi; Takeshita, Katsushi; Inoue, Hirokazu; Maekawa, Asato; Endo, Kenji; Miyamoto, Takuya; Furuya, Takeo; Nakamura, Akira; Mori, Kanji; Kanbara, Shunsuke; et al.
Abstract : Study Design: Prospective multicenter study. Objective: The aim of this study was to compare the clinical and radiographic results of laminoplasty (LAMP), anterior decompression with fusion (ADF), and posterior decompression with fusion (PDF) for degenerative cervical myelopathy (DCM). Summary of Background Data: Although ADF, LAMP, and PDF have been performed for DCM, little is known about the difference in impact of these surgical treatments on clinical and radiographic outcomes. Methods: We prospectively enrolled patients who were scheduled for surgery for DCM and compared the clinical and radiographic results of ADF, LAMP, and PDF. Results: In total, 171 patients completed the 1-year follow-up. Regarding clinical outcomes, the Japanese Orthopedic Association score for the assessment of cervical myelopathy (C-JOA score), European Quality of Life-5 Dimensions (EQ-5D), and Neck Disability Index (NDI) scores improved in all groups postoperatively. However, no significant differences were found in C-JOA, EQ-5D, and NDI scores and recovery rate among the groups. Regarding radiographic parameters, although the operation had no effect on cervical lordosis (CL) and the C2–7 sagittal vertical axis (SVA) in the ADF group, they worsened in the LAMP and PDF group. Although there were no significant differences in any preoperative radiographic parameters within the ADF and LAMP group, CL was significantly lower and the C2–7 SVA was significantly higher in the nonrecovery group within the PDF group. Logistic regression analysis showed that preoperative lower CL was an independent risk factor for poor recovery in the PDF group. Conclusion: Although groups showed no significant differences in clinical outcomes, cervical alignment worsened after surgery in the LAMP and PDF groups. Within the PDF group, lower CL was an independent risk factor for poor recovery. Therefore, the indications for PDF in DCM patients with preoperative kyphotic alignment should be carefully considered. Level of Evidence: 3